Quality of life in patients with temporomandibular joint arthrosis and orthopedic treatment of missing teeth depending on the severity of arthrosis and implant volume - Balykov, V.; Shakhnovskyi, I.; Burdeinyi, V.; Cherednychenko, A.; Lysenko, V.; Nazarov, O.; Rozhko, P. (Journal of Education, Health and Sport, 2024)
Temporomandibular (TMJ) arthrosis severely impacts everyday activity and has substantial negative consequences for the general health state, especially when local manifestations are orchestrated by pronounced pain syndrome. That justifies the necessity of investigating the quality of life (QL) of patients with TMJ arthrosis who are undergoing orthopedic treatment. The research aimed to investigate the QL of patients with unilateral and bilateral TMJ arthrosis before and 6-8 months after occlusion correction, which was achieved by placing a different number of implants. In total, 127 patients (75 women and 52 men) were observed in the study of quality of life indicators, which were divided into four groups: bilateral TMJ arthrosis with the implantation of 3-6 implants (36 patients); bilateral TMJ arthrosis with the implantation of 1-2 implants (30 patients); unilateral TMJ arthrosis with the implantation of 3-6 implants (29 patients); unilateral TMJ arthrosis with the implantation of 1-2 implants (32 patients). Each group was comparable in age, gender, duration, and manifestations of arthrosis. QL was measured using questionnaire SF-36. In patients who were diagnosed with bilateral TMJ arthrosis and underwent implantation of 3-6 implants in the postponed period, only pain (P) and SRF scales significantly exceeded initial values – by two times and by 23.2% correspondently (P<0.05). In patients with bilateral TMJ arthrosis and implantation of 1-2 implants showed significant increase on all scales except PF and MH. Thus, the implantation of a significant number of implants (3-6) in the setting of unilateral manifestations of TMJ arthrosis showed an improvement in the quality of life of patients compared to the baseline level on five scales - PF, P, Vit, SRF and RLEH (P<0.05). In patients with unilateral TMJ arthrosis and a small number (1-2) of implant insertions, initial QL was relatively better when compared with other groups, and posttreatment improvement was seen in all scales (P<0.05). The results indicated the effectiveness of improving the quality of life by correcting the occlusion using permanent implants in patients with manifestations of TMJ arthrosis. The severity of the therapeutic effect has an inversely proportional relationship with the severity of the manifestations of arthrosis and the amount of orthopedic care provided. The obtained results indicate the effectiveness of the SF-36 questionnaire in orthopedic patients with TMJ arthrosis and general distinct health disorders.